P242 Anxiolytic and antidepressant use among court workers in minas gerais, brazil. (1st September 2016) - Lima, Eduardo; Costa, Bruna; Assunção, Ada
Abstract : The use of anxiolytics and antidepressants indicates the presence of psychiatric morbidity among active workers in labour market. When used without proper orientation (self-medication), the consumption of these substances can exacerbate or cause more serious conditions, intoxication and dependence. Occupational stressors can be related to psychiatric medication use, including self-medication. Cross-sectional study, with random and representative sample, was held at Minas Gerais State Court, Brazil. The aim was to investigate psychosocial factors associated with psychiatric self-medication among State Court workers. All permanent workers (n = 12, 251) who were working in the 296 Minas Gerais law districts were eligible. The estimation of the sample size (n = 1000) considered the following parameters: number of workers, prevalence of sick leave of 40% and 95% confidence interval. A stratified proportional random sampling was performed. Data was collected by telephone survey, including socioeconomic, occupational, and health information. Among the occupational variables we call atention to eletronic tools use, job demands, work control and social support. Logistic regression analysis indicated associations between psychiatric self-medication and occupational variables. Our findings suggested that work intensification was associated with self-medication use. Health policies focusing on controlling and monitoring psychosocial factors at work in Brazilian judiciary services are desirable.